The Effect of Nurturing Narratives on Language and Cognition in Children With Social Communication Disorder: A Single-Subject Study. - Nikrah, Pegah; Nakhshab, Mahbubeh; Chahie, Rasool Ghareh (Journal of Monolingual & Bilingual Speech (JMBS), 2026)
The narrative abilities of children are predictive of academic success and social adjustment. In this study, the nurturing narratives (NN) approach was evaluated for its ability to lead to language and cognitive development in children with a social communication disorder (SCD). A single-subject study involved three Persian-speaking SCD subjects aged 3.6 to 6 years. All subjects received 12 intervention sessions. They also attended six assessment sessions. Each subject's story level was determined by using an NN entry-level checklist. Personal narratives for each subject were individualized based on their event knowledge. A pre- and post-test of the PANA was also used to evaluate cognitive and language skills. One or two story components were targeted in each intervention session. Improvement rate difference (IRD) and visual analysis report the effect size. There was a significant improvement in contextualization, theory of mind, story memory, and vocabulary (IRD > 50%). On the other hand, this effect was not considered in event knowledge, story text, and inferencing (IRD < 50%). Moreover, the PANA showed that the NN approach was effective in attention, morphological, play, and phonological skills.